Acidophilous dry grasslands on the quartzite bedrock in western Slovakia - Dúbravková, Daniela; Košťál, Jaroslav (Hacquetia, 2015)
The paper presents results of actual phytocoenological research of acidophilous dry grasslands of the Koelerio- Phleion phleoidis Korneck 1974 alliance on the quartzite bedrock in western Slovakia. The modified TWINSPAN analysis distinguished two associations in the study area. Avenulo pratensis-Festucetum valesiacae Vicherek et al. in Chytrý et al. 1997 is dominated by Festuca valesiaca s.l. and it is distributed on the quartzite hills in the Tribeč Mts. Potentillo heptaphyllae-Festucetum rupicolae (Klika 1951) Toman 1970 occurs at sites in the Biele Karpaty Mts and Považský Inovec Mts and it is dominated by Festuca rupicola. The paper brings very first data on distribution of Avenulo pratensis-Festucetum valesiacae in Slovakia and extends knowledge on occurrence of Potentillo heptaphyllae-Festucetum rupicolae. Both associations represent very rare vegetation types of Central Europe. In Slovakia, they occur locally at small sized stands and are threatened by successional changes caused by cessation of traditional management and island occurrence within other vegetation types. Main environmental gradients responsible for variation in species composition of these grasslands were revealed by the principal component analysis (PCA) and interpreted using indicator values and measured characteristics of the study sites. The major pattern of variation reflects altitude, which is negatively correlated with temperature and soil depth. The relationship between species composition and environmental factors (pedology, topography, geographical position) was analysed by redundancy analysis (RDA). The most important factor affecting the data variation was longitude followed by soil pH, slope and latitude.